Woodpecker Poles and Habitat Wood in Your Yard - Benjamin Schwartz; Jiri Hulcr; Andrew Koeser; Stan Rosenthal (EDIS)
This publication provides a practical guide for homeowners and professional arborists to maintain dead wood habitat on their or their clients’ property. It outlines the environmental and financial benefits of keeping dead wood, the different types of habitat one can manage, and strategies for mitigating the risk associated with dead wood.